Novel Small Molecule Tyrosine Kinase 2 Pseudokinase Ligands Block Cytokine-Induced TYK2-Mediated Signaling Pathways - Zhou, Yu; Li, Xin; Shen, Ru; Wang, Xiangzhu; Zhang, Fan; Liu, Suxing; Li, Di; Liu, Jian; Li, Puhui; Yan, Yinfa; Dong, Ping; Zhang, Zhigao; et al. (Frontiers in Immunology, 2022)
A member of the Janus kinase (JAK) family, Tyrosine Kinase 2 (TYK2), is crucial in mediating various cytokine-signaling pathways such as interleukin-23 (IL23), interleukin-12 (IL12) and type I Interferons (IFN) which contribute to autoimmune disorders (e.g., psoriasis, lupus, and inflammatory bowel disease). Thus, TYK2 represents an attractive target to develop small-molecule therapeutics for the treatment of cytokine-driven inflammatory diseases. Selective inhibition of TYK2 over other JAK isoforms is critical to achieve a favorable therapeutic index in the development of TYK2 inhibitors. However, designing small molecule inhibitors to target the ATP binding site of TYK2 kinase has been challenging due to the substantial structural homology of the JAK family catalytic domains. Here, we employed an approach to target the JAK homology 2 (JH2) pseudokinase regulatory domain of the TYK2 protein. We developed a series of small-molecule TYK2 pseudokinase ligands, which suppress the TYK2 catalytic activity through allosteric regulation. The TYK2 pseudokinase-binding small molecules in this study simultaneously achieve high affinity-binding for the TYK2 JH2 domain while also affording significantly reduced affinity for the TYK2 JAK homology 1 (JH1) kinase domain. These TYK2 JH2 selective molecules, although possessing little effect on suppressing the catalytic activity of the isolated TYK2 JH1 catalytic domain in the kinase assays, can still significantly block the TYK2-mediated receptor-stimulated pathways by binding to the TYK2 JH2 domain and allosterically regulating the TYK2 JH1 kinase. These compounds are potent towards human T-cell lines and primary immune cells as well as in human whole-blood specimens. Moreover, TYK2 JH2-binding ligands exhibit remarkable selectivity of TYK2 over JAK isoforms not only biochemically but also in a panel of receptor-stimulated JAK1/JAK2/JAK3-driven cellular functional assays. In addition, the TYK2 JH2-targeting ligands also demonstrate high selectivity in a multi-kinase screening panel. The data in the current study underscores that the TYK2 JH2 pseudokinase is a promising therapeutic target for achieving a high degree of biological selectivity. Meanwhile, targeting the JH2 domain represents an appealing strategy for the development of clinically well-tolerated TYK2 inhibitors that would have superior efficacy and a favorable safety profile compared to the existing Janus kinase inhibitors against autoimmune diseases.